A new energy vehicle PCB coated with a protective film and its preparation process
By using the protection coatings prepared by modified epoxy resin on the PCB board, and combined with the ceramic substrate technology of porous aluminum powder, the existing PCB protective coating adhesion and insufficient high temperature resistance have been solved, and it has achieved more efficient efficiency. The protection effect.
Patent Information
- Application Number
- CN202311163693.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-11
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-09-11
AI Technical Summary
The existing PCB protective coatings have insufficient adhesion and poor high temperature resistance, so they cannot effectively protect PCB boards, especially in high temperature environments.
A new energy vehicle PCB preparation process with a protective film is used to add calcium carbonate and sodium carbonate, and to mix with three water aluminum, carbon powder and other materials, and mix with ball mills to form pores. Based on the ceramic substrate, the copper foil is fitted and the post -work process is processed, and the protective coatings are prepared with modified epoxy resin and sprayed on the surface of the PCB plate.
It significantly improves the adhesion, corrosion resistance and high temperature resistance of the protective film, thereby better protecting the PCB board and extending its service life.
Smart Images

Figure CN117677046B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of PCBs, and in particular to a new energy vehicle PCB coated with a protective film and a preparation process thereof. Background Art
[0002] PCB, or printed circuit board, is a widely used electronic component. It is the support of electronic components and the carrier of electrical connections. It is widely used in the field of electronic products due to its high density, high reliability, designability and assemblability.
[0003] At present, the existing PCB protective coatings can be divided into five types: acrylic, epoxy resin, polyurethane, silicone and paraxylene. However, these types of protective coatings have insufficient adhesion to PCB boards and poor high temperature resistance. Once the ambient temperature is too high during the use of the PCB board, the protective coating will be damaged, thereby affecting its protective effect on the PCB board.
[0004] Therefore, we propose a new energy vehicle PCB coated with a protective film having good adhesion and high temperature corrosion resistance and a preparation process thereof to better protect the PCB board. Summary of the invention
[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a new energy vehicle PCB coated with a protective film and a preparation process thereof.
[0006] A preparation process of a new energy vehicle PCB coated with a protective film comprises the following steps:
[0007] S1: Add calcium carbonate and sodium carbonate and mix
[0008] Grind and mix gibbsite and carbon powder, then add calcium carbonate and sodium carbonate, and disperse at high speed, then add boric acid and water glass, and mix by ball milling to obtain a mixed slurry;
[0009] S2: Pressing and sintering
[0010] The mixed slurry is pressed, sintered in a hydrogen atmosphere, and then further sintered in an air atmosphere, and then crushed and ground to obtain porous alumina powder;
[0011] S3: ball milling and slip casting
[0012] Sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, carboxymethyl cellulose and deionized water are mixed, and then ball-milled with the porous alumina powder, and then slip-casted and sintered to obtain a ceramic substrate;
[0013] S4: Paste copper foil and perform post-processing
[0014] A thin layer of resin glue is evenly coated on the above ceramic base surface, and then copper foil is attached to the upper and lower surfaces of the ceramic substrate coated with resin glue to obtain a foil-clad board, and then the foil-clad board is processed through a post-process to obtain a precursor PCB board;
[0015] S5: Silicone and carbon dioxide modified epoxy resin
[0016] The epoxy resin, the organosilicon, the catalyst and the deionized water are mixed, heated and stirred to react, so as to obtain a primary modified epoxy resin, and then carbon dioxide is introduced into the primary modified epoxy resin to continue the reaction, so as to obtain a secondary modified epoxy resin;
[0017] S6: Prepare and spray protective coating
[0018] The secondary modified epoxy resin is mixed with polyoxypropylene diamine, a leveling agent, a defoaming agent, a dispersant and a filler to prepare a protective coating, and then the protective coating is evenly sprayed on the surface of the precursor PCB board. After drying and curing, a new energy vehicle PCB coated with a protective film is obtained.
[0019] Furthermore, the step S1 of adding calcium carbonate and sodium carbonate and mixing them specifically comprises the following steps:
[0020] S1.1: Add gibbsite and carbon powder into a grinder at a mass ratio of 10-12:1 and grind for 2-3 hours to obtain a primary mixed powder;
[0021] S1.2: Open the discharge valve of the grinder and pour the above-mentioned primary mixed powder into the high-speed disperser. When the gravity sensor in the high-speed disperser detects that the gravity in the machine begins to increase, the gravity sensor sends a signal to the controller;
[0022] S1.3: After receiving the signal sent by the gravity sensor, the controller controls the feeding component to add calcium carbonate and sodium carbonate into the high-speed disperser at a mass ratio of 1-2:1;
[0023] S1.4: until the gravity sensor detects that the gravity in the machine is no longer increasing, the gravity sensor sends a signal to the controller again;
[0024] S1.5: After receiving the signal sent by the gravity sensor again, the controller controls the high-speed disperser to disperse at a rate of 3000-4000 r / min for 30-50 min to obtain a secondary mixed powder;
[0025] S1.6: The controller controls the discharging component of the high-speed disperser to start, pours the secondary mixed powder into the ball mill, and then adds boric acid and water glass into the ball mill, and ball mills for 1-2 hours to obtain a mixed slurry.
[0026] Furthermore, the pressing and sintering in step S2 specifically includes the following steps:
[0027] S2.1: injecting the mixed slurry obtained in step S1.6 into a mold, and then pressing it with a uniaxial press at a pressure of 80-100 MPa to obtain a compact;
[0028] S2.2: placing the compacted body in a sintering furnace, and then starting the ventilation assembly to extract the air in the sintering furnace through the ventilation assembly, and then replenishing dry hydrogen into the sintering furnace;
[0029] S2.3: until the air pressure sensor in the furnace detects that the air pressure in the furnace returns to the initial state, the air pressure sensor sends a signal to the controller;
[0030] S2.4: After receiving the signal sent by the air pressure sensor, the controller controls the ventilation component to close, and controls the sintering furnace to heat at a temperature of 1500-1800°C for 1-2h;
[0031] S2.5: Keeping the heating temperature unchanged, the controller controls the ventilation component to open, exhaust the gas in the furnace through the ventilation component, and then replenish dry air into the furnace;
[0032] S2.6: until the air pressure sensor in the furnace detects that the air pressure in the furnace returns to the initial state, the air pressure sensor sends a signal to the controller again;
[0033] S2.7: After the controller receives the signal sent by the air pressure sensor again, it controls the sintering furnace to continue sintering for 1-2 hours to obtain a porous alumina compact;
[0034] S2.8: Place the porous alumina compact in a crushing and grinding machine to crush and grind the porous alumina powder.
[0035] Furthermore, the ball milling and slurry injection molding in step S3 specifically includes the following steps:
[0036] S3.1: Sodium dodecyl sulfate, hexadecyl trimethyl ammonium bromide, carboxymethyl cellulose and deionized water are added into a mixing tank in a volume ratio of 20-22:13-15:8-10:40-50, and stirred to obtain a mixed solution;
[0037] S3.2: Open the discharge valve of the crushing and grinding machine, pour the porous alumina powder obtained in step S2.8 into the ball mill, and add the above mixed solution into the ball mill, and ball mill for 30-40 minutes to obtain a mixed slurry;
[0038] S3.3: pouring the mixed slurry into a plaster mold for slurry injection molding, and after demoulding, obtaining a slab material;
[0039] S3.4: placing the above-mentioned slab material into an oven for drying, and then placing the dried slab material into a sintering furnace for sintering at 1500-1600° C. for 2-3 hours to obtain a ceramic substrate.
[0040] Furthermore, the step S5 of modifying the epoxy resin with organic silicon and carbon dioxide respectively comprises the following steps:
[0041] S5.1: Add epoxy resin, organosilicon, catalyst and deionized water into the reactor, and then introduce nitrogen into the reactor until all the air in the reactor is exhausted;
[0042] S5.2: Turn on the heater and stirrer in the reactor, heat and stir at a temperature of 100-120°C and a rate of 300-400 r / min, react for 3-5 hours, extract the catalyst with high-purity water 2-4 times, and then perform reduced pressure distillation to obtain a primary modified epoxy resin;
[0043] S5.3: Add the primary modified epoxy resin and tetrabutylammonium bromide into a high-pressure reactor, and then introduce carbon dioxide into the reactor until all the air in the reactor is exhausted;
[0044] S5.4: Start the high-pressure reactor, heat and stir, and continue to introduce carbon dioxide into the reactor until the pressure in the reactor reaches 1.6-2.2 MPa. React for 3-4 hours to obtain a secondary modified epoxy resin.
[0045] Furthermore, the preparation and spraying of the protective coating in step S6 specifically includes the following steps:
[0046] S6.1: Add the secondary modified epoxy resin obtained in step S5.4 into a mixer, and then add polyoxypropylene diamine, a leveling agent, a defoamer, a dispersant and a filler into the mixer, and stir at a rate of 1000-1200 r / min for 1-2 hours to obtain a protective coating;
[0047] S6.2: Spray the protective coating evenly on the surface of the front drive PCB board by an automatic spraying machine to form a protective layer;
[0048] S6.3: Place the precursor PCB sheet with a protective layer on the surface in an oven, set the oven drying temperature to 70-90°C, dry for 3-5 hours, and after the protective layer is cured, obtain a new energy vehicle PCB coated with a protective film.
[0049] Furthermore, the organosilicon is prepared by mixing diphenylsilanediol and DC-3074 in a mass ratio of 1:2-3.
[0050] Furthermore, the catalyst is dibutyltin dilaurate.
[0051] Furthermore, the atomizing valve pressure of the automatic spraying machine is 0.4-0.6MPa, the moving speed of the glue valve is 40000-48000μm / min, the height of the atomizing valve from the PCB board is 12-15mm, and the spraying speed is 80000-100000μm / min.
[0052] Furthermore, a new energy vehicle PCB coated with a protective film is prepared by any of the above-mentioned preparation processes for a new energy vehicle PCB coated with a protective film.
[0053] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0054] 1. The present invention uses organic silicon to modify the epoxy resin once, then introduces carbon dioxide to react for secondary modification, and then adds polyoxypropylene diamine, a leveling agent, a defoaming agent, a dispersant and a filler to prepare a protective coating, which can better improve its adhesion, corrosion resistance and high temperature resistance, thereby better protecting the PCB board and extending the service life of the PCB board.
[0055] 2. The present invention prepares porous alumina by fully ball-milling gibbsite with carbon powder, calcium carbonate, sodium carbonate, boric acid and water glass, and sintering them in hydrogen and air respectively. The PCB substrate prepared by using the porous alumina as a raw material has excellent high temperature resistance and acid and alkali corrosion resistance, and can further expand the application range of the prepared PCB board.
[0056] 3. The present invention can maintain the electrical insulation stability of the ceramic substrate at high temperature by adding calcium carbonate to the crushed gibbsite, thereby preventing the performance of the ceramic substrate from being affected by excessive temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1 This is a process flow chart of the preparation of a new energy vehicle PCB coated with a protective film used in an embodiment of the present invention.
[0058] Figure 2 The following is a summary table of performance test results of Example 1, Example 2 and Example 3 of the present invention.
[0059] Figure 3 The following is a summary table of the performance test results of Example 1 and Comparative Example 1 of the present invention.
[0060] Figure 4 The following is a summary table of the performance test results of Example 1 and Comparative Example 2 of the present invention.
[0061] Figure 5 The following is a summary table of the performance test results of Example 1 and Comparative Example 3 of the present invention.
[0062] Figure 6The following is a summary table of the performance test results of Example 1 and Comparative Example 4 of the present invention. DETAILED DESCRIPTION
[0063] The present invention is further described in detail below with reference to specific embodiments.
[0064] Example 1
[0065] A preparation process for a new energy vehicle PCB coated with a protective film, such as Figure 1 and Figure 2 As shown, the following steps are included:
[0066] S1: Add calcium carbonate and sodium carbonate and mix
[0067] Add gibbsite and carbon powder to the grinder at a mass ratio of 10:1, grind for 2 hours to obtain a primary mixed powder, then open the discharge valve of the grinder, pour the primary mixed powder into the high-speed disperser, when the gravity sensor in the high-speed disperser detects that the gravity in the machine begins to increase, the gravity sensor sends a signal to the controller, after the controller receives the signal sent by the gravity sensor, controls the feeding component to add calcium carbonate and sodium carbonate into the high-speed disperser at a mass ratio of 1:1, until the gravity sensor detects that the gravity in the machine no longer increases, the gravity sensor sends a signal to the controller again, after the controller receives the signal sent by the gravity sensor again, controls the high-speed disperser to disperse at a rate of 3000r / min for 30 minutes, to obtain a secondary mixed powder, then, the controller controls the discharge component of the high-speed disperser to open, pour the secondary mixed powder into the ball mill, then add boric acid and water glass to the ball mill, ball mill for 1 hour, to obtain a mixed slurry;
[0068] S2: Pressing and sintering
[0069] The mixed slurry is injected into a mold, and then pressed at a pressure of 80 MPa by a uniaxial press to obtain a compact, and then the compact is placed in a sintering furnace, and then the ventilation component is started, and the air in the sintering furnace is extracted through the ventilation component, and then dry hydrogen is added to the sintering furnace until the air pressure sensor in the furnace detects that the air pressure in the furnace returns to the initial state, and the air pressure sensor sends a signal to the controller. After the controller receives the signal sent by the air pressure sensor, it controls the ventilation component to close, and controls the sintering furnace to heat at a temperature of 1500°C for 1h, and then keeps the heating temperature unchanged. The controller controls the ventilation component to open, and the gas in the furnace is discharged through the ventilation component, and then dry air is added to the furnace until the air pressure sensor in the furnace detects that the air pressure in the furnace returns to the initial state again, and the air pressure sensor sends a signal to the controller again. After the controller receives the signal sent by the air pressure sensor again, it controls the sintering furnace to continue sintering for 1h to obtain a porous alumina compact. Finally, the porous alumina compact is placed in a crushing and grinding machine for crushing and grinding to obtain a porous alumina powder.
[0070] S3: ball milling and slip casting
[0071] Sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, carboxymethyl cellulose and deionized water are added into a mixing tank at a volume ratio of 20:13:8:40, stirred and mixed to obtain a mixed solution, then the discharge valve of the crushing and grinding machine is opened, the porous alumina powder is poured into the ball mill, and the mixed solution is added into the ball mill, ball milled for 30 minutes to obtain a mixed slurry, and then the mixed slurry is poured into a gypsum mold for slip injection molding, and after demolding, a slab material is obtained, and then the slab material is placed in an oven for drying, and then the dried slab material is placed in a sintering furnace and sintered at 1500° C. for 2 hours to obtain a ceramic substrate;
[0072] S4: Paste copper foil and perform post-processing
[0073] A thin layer of resin glue is evenly coated on the above ceramic base surface, and then copper foil is attached to the upper and lower surfaces of the ceramic substrate coated with resin glue to obtain a foil-clad board, and then the foil-clad board is processed through a post-process to obtain a precursor PCB board;
[0074] S5: Silicone and carbon dioxide modified epoxy resin
[0075] An epoxy resin, an organosilicon prepared by mixing diphenylsilanediol and DC-3074 in a mass ratio of 1:2, dibutyltin dilaurate and deionized water are added to a reactor, and nitrogen is introduced into the reactor until the air in the reactor is exhausted, and then the heater and the stirrer in the reactor are turned on, and the mixture is heated and stirred at a temperature of 100° C. and a rate of 300 r / min. After reacting for 3 hours, the catalyst is extracted twice with high-purity water, and then vacuum distillation is performed to obtain a primary modified epoxy resin, and then the primary modified epoxy resin and tetrabutylammonium bromide are added to a high-pressure reactor, and carbon dioxide is introduced into the reactor until the air in the reactor is exhausted, and then the high-pressure reactor is started, heated and stirred, and carbon dioxide is continuously introduced into the reactor until the air pressure in the reactor reaches 1.6 MPa, and the reaction is performed for 3 hours to obtain a secondary modified epoxy resin;
[0076] S6: Prepare and spray protective coating
[0077] The secondary modified epoxy resin is added to a mixer, and then polyoxypropylene diamine, leveling agent, defoamer, dispersant and filler are added to the mixer, and stirred at a rate of 1000r / min for 1h to obtain a protective coating. Then, the atomizing valve pressure of the automatic sprayer is set to 0.4MPa, the glue valve moving speed is set to 40000μm / min, the height of the atomizing valve from the PCB board is set to 12mm, and the spraying speed is set to 80000μm / min. The protective coating is evenly sprayed on the surface of the precursor PCB board by the automatic sprayer to form a protective layer. Finally, the precursor PCB board with the protective layer on the surface is placed in an oven, the drying temperature of the oven is set to 70°C, and it is dried for 3h. After the protective layer is cured, a new energy vehicle PCB coated with a protective film is obtained.
[0078] Then, various performance tests were performed on the prepared new energy vehicle PCB coated with the protective film:
[0079] First, the adhesion of the protective film of the prepared new energy vehicle PCB was tested according to the method in the national standard GB / T17-1979. The results showed that its adhesion was level one.
[0080] Then, the corrosion resistance of the protective film of the prepared new energy vehicle PCB was tested according to the method in the national standard GB / T1771-1991. The results showed that it could withstand neutral salt spray for about 1689 hours.
[0081] Finally, a thermogravimetric analyzer was used to test the high temperature resistance of the protective film for the prepared new energy vehicle PCB. The results showed that it can withstand a high temperature of about 750°C.
[0082] Example 2
[0083] A preparation process for a new energy vehicle PCB coated with a protective film, such as Figure 1 and Figure 2 As shown, the following steps are included:
[0084] S1: Add calcium carbonate and sodium carbonate and mix
[0085] Add gibbsite and carbon powder to the grinder at a mass ratio of 11:1, grind for 2.5 hours to obtain a primary mixed powder, then open the discharge valve of the grinder, pour the primary mixed powder into the high-speed disperser, when the gravity sensor in the high-speed disperser detects that the gravity in the machine begins to increase, the gravity sensor sends a signal to the controller, after the controller receives the signal sent by the gravity sensor, controls the feeding component to add calcium carbonate and sodium carbonate into the high-speed disperser at a mass ratio of 1.5:1, until the gravity sensor detects that the gravity in the machine no longer increases, the gravity sensor sends a signal to the controller again, after the controller receives the signal sent by the gravity sensor again, controls the high-speed disperser to disperse at a rate of 3500r / min for 40 minutes, to obtain a secondary mixed powder, then, the controller controls the discharge component of the high-speed disperser to open, pour the secondary mixed powder into the ball mill, then add boric acid and water glass to the ball mill, ball mill for 1.5 hours, to obtain a mixed slurry;
[0086] S2: Pressing and sintering
[0087] The mixed slurry is injected into a mold, and then pressed by a uniaxial press at a pressure of 90 MPa to obtain a compact, and then the compact is placed in a sintering furnace, and then the ventilation component is started, and the air in the sintering furnace is extracted through the ventilation component, and then dry hydrogen is added to the sintering furnace until the air pressure sensor in the furnace detects that the air pressure in the furnace returns to the initial state, and the air pressure sensor sends a signal to the controller. After the controller receives the signal sent by the air pressure sensor, it controls the ventilation component to close, and controls the sintering furnace to heat at a temperature of 1650° C. for 1.5 hours, and then keeps the heating temperature unchanged. The controller controls the ventilation component to open, and the gas in the furnace is discharged through the ventilation component, and then dry air is added to the furnace until the air pressure sensor in the furnace detects that the air pressure in the furnace returns to the initial state again, and the air pressure sensor sends a signal to the controller again. After the controller receives the signal sent by the air pressure sensor again, it controls the sintering furnace to continue sintering for 1.5 hours to obtain a porous alumina compact. Finally, the porous alumina compact is placed in a crushing and grinding machine for crushing and grinding to obtain a porous alumina powder.
[0088] S3: ball milling and slip casting
[0089] Sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, carboxymethyl cellulose and deionized water are added into a mixing tank in a volume ratio of 21:14:9:45, stirred and mixed to obtain a mixed solution, then the discharge valve of the crushing and grinding machine is opened, the porous alumina powder is poured into the ball mill, and the mixed solution is added into the ball mill, ball milled for 35 minutes to obtain a mixed slurry, and then the mixed slurry is poured into a gypsum mold for slip injection molding, and after demolding, a slab material is obtained, and then the slab material is placed in an oven for drying, and then the dried slab material is placed in a sintering furnace and sintered at 1550° C. for 2.5 hours to obtain a ceramic substrate;
[0090] S4: Paste copper foil and perform post-processing
[0091] A thin layer of resin glue is evenly coated on the above ceramic base surface, and then copper foil is attached to the upper and lower surfaces of the ceramic substrate coated with resin glue to obtain a foil-clad board, and then the foil-clad board is processed through a post-process to obtain a precursor PCB board;
[0092] S5: Silicone and carbon dioxide modified epoxy resin
[0093] An epoxy resin, an organosilicon prepared by mixing diphenylsilanediol and DC-3074 in a mass ratio of 1:2.5, dibutyltin dilaurate and deionized water are added to a reactor, and nitrogen is introduced into the reactor until the air in the reactor is exhausted, and then the heater and the stirrer in the reactor are turned on, and the mixture is heated and stirred at a temperature of 110° C. and a rate of 350 r / min. After reacting for 4 hours, the catalyst is extracted 3 times with high-purity water, and then vacuum distillation is performed to obtain a primary modified epoxy resin, and then the primary modified epoxy resin and tetrabutylammonium bromide are added to a high-pressure reactor, and carbon dioxide is introduced into the reactor until the air in the reactor is exhausted, and then the high-pressure reactor is started, heated and stirred, and carbon dioxide is continuously introduced into the reactor until the air pressure in the reactor reaches 1.9 MPa, and the reaction is performed for 3.5 hours to obtain a secondary modified epoxy resin;
[0094] S6: Prepare and spray protective coating
[0095] The secondary modified epoxy resin is added to a mixer, and then polyoxypropylene diamine, leveling agent, defoamer, dispersant and filler are added to the mixer, and stirred at a rate of 1100r / min for 1.5h to obtain a protective coating. Then, the atomizing valve pressure of the automatic sprayer is set to 0.5MPa, the glue valve moving speed is set to 44000μm / min, the height of the atomizing valve from the PCB board is set to 13.5mm, and the spraying speed is set to 90000μm / min. The protective coating is evenly sprayed on the surface of the precursor PCB board by the automatic sprayer to form a protective layer. Finally, the precursor PCB board with the protective layer on the surface is placed in an oven, the drying temperature of the oven is set to 80°C, and it is dried for 4h. After the protective layer is cured, a new energy vehicle PCB coated with a protective film is obtained.
[0096] Then, various performance tests were performed on the prepared new energy vehicle PCB coated with the protective film:
[0097] First, the adhesion of the protective film of the prepared new energy vehicle PCB was tested according to the method in the national standard GB / T17-1979. The results showed that its adhesion was level one.
[0098] Then, the corrosion resistance of the protective film of the prepared new energy vehicle PCB was tested according to the method in the national standard GB / T1771-1991. The results showed that it could withstand neutral salt spray for about 1703h.
[0099] Finally, a thermogravimetric analyzer was used to test the high temperature resistance of the protective film for the prepared new energy vehicle PCB. The results showed that it could withstand a high temperature of about 745°C.
[0100] Example 3
[0101] A preparation process for a new energy vehicle PCB coated with a protective film, such as Figure 1 and Figure 2 As shown, the following steps are included:
[0102] S1: Add calcium carbonate and sodium carbonate and mix
[0103] Add gibbsite and carbon powder to the grinder at a mass ratio of 12:1, grind for 3 hours to obtain a primary mixed powder, then open the discharge valve of the grinder, pour the primary mixed powder into the high-speed disperser, when the gravity sensor in the high-speed disperser detects that the gravity in the machine begins to increase, the gravity sensor sends a signal to the controller, after the controller receives the signal sent by the gravity sensor, controls the feeding component to add calcium carbonate and sodium carbonate into the high-speed disperser at a mass ratio of 2:1, until the gravity sensor detects that the gravity in the machine no longer increases, the gravity sensor sends a signal to the controller again, after the controller receives the signal sent by the gravity sensor again, controls the high-speed disperser to disperse at a rate of 4000r / min for 50 minutes, to obtain a secondary mixed powder, then, the controller controls the discharge component of the high-speed disperser to open, pour the secondary mixed powder into the ball mill, then add boric acid and water glass to the ball mill, ball mill for 2 hours, to obtain a mixed slurry;
[0104] S2: Pressing and sintering
[0105] The mixed slurry is injected into a mold, and then pressed at a pressure of 100 MPa by a uniaxial press to obtain a compact, and then the compact is placed in a sintering furnace, and then the ventilation component is started, and the air in the sintering furnace is extracted through the ventilation component, and then dry hydrogen is added to the sintering furnace until the air pressure sensor in the furnace detects that the air pressure in the furnace returns to the initial state, and the air pressure sensor sends a signal to the controller. After the controller receives the signal sent by the air pressure sensor, it controls the ventilation component to be closed, and controls the sintering furnace to heat at a temperature of 1800°C for 2h, and then keeps the heating temperature unchanged. The controller controls the ventilation component to open, and the gas in the furnace is discharged through the ventilation component, and then dry air is added to the furnace until the air pressure sensor in the furnace detects that the air pressure in the furnace returns to the initial state again, and the air pressure sensor sends a signal to the controller again. After the controller receives the signal sent by the air pressure sensor again, it controls the sintering furnace to continue sintering for 2h to obtain a porous alumina compact. Finally, the porous alumina compact is placed in a crushing and grinding machine for crushing and grinding to obtain a porous alumina powder.
[0106] S3: ball milling and slip casting
[0107] Sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, carboxymethyl cellulose and deionized water are added into a mixing tank at a volume ratio of 22:15:10:50, stirred and mixed to obtain a mixed solution, then the discharge valve of the crushing and grinding machine is opened, the porous alumina powder is poured into the ball mill, and the mixed solution is added into the ball mill, ball milled for 40 minutes to obtain a mixed slurry, and then the mixed slurry is poured into a gypsum mold for slip injection molding, and after demolding, a slab material is obtained, and then the slab material is placed in an oven for drying, and then the dried slab material is placed in a sintering furnace and sintered at 1600° C. for 3 hours to obtain a ceramic substrate;
[0108] S4: Paste copper foil and perform post-processing
[0109] A thin layer of resin glue is evenly coated on the above ceramic base surface, and then copper foil is attached to the upper and lower surfaces of the ceramic substrate coated with resin glue to obtain a foil-clad board, and then the foil-clad board is processed through a post-process to obtain a precursor PCB board;
[0110] S5: Silicone and carbon dioxide modified epoxy resin
[0111] An epoxy resin, an organosilicon prepared by mixing diphenylsilanediol and DC-3074 in a mass ratio of 1:3, dibutyltin dilaurate and deionized water are added to a reactor, and nitrogen is introduced into the reactor until the air in the reactor is exhausted, and then the heater and the stirrer in the reactor are turned on, and the mixture is heated and stirred at a temperature of 120° C. and a rate of 400 r / min. After reacting for 5 hours, the catalyst is extracted 4 times with high-purity water, and then vacuum distillation is performed to obtain a primary modified epoxy resin, and then the primary modified epoxy resin and tetrabutylammonium bromide are added to a high-pressure reactor, and carbon dioxide is introduced into the reactor until the air in the reactor is exhausted, and then the high-pressure reactor is started, heated and stirred, and carbon dioxide is continuously introduced into the reactor until the air pressure in the reactor reaches 2.2 MPa, and the reaction is performed for 4 hours to obtain a secondary modified epoxy resin;
[0112] S6: Prepare and spray protective coating
[0113] The secondary modified epoxy resin is added to a mixer, and then polyoxypropylene diamine, leveling agent, defoamer, dispersant and filler are added to the mixer, and stirred at a rate of 1200r / min for 2h to obtain a protective coating. Then, the atomizing valve pressure of the automatic sprayer is set to 0.6MPa, the glue valve moving speed is set to 48000μm / min, the height of the atomizing valve from the PCB board is set to 15mm, and the spraying speed is set to 100000μm / min. The protective coating is evenly sprayed on the surface of the precursor PCB board by the automatic sprayer to form a protective layer. Finally, the precursor PCB board with the protective layer on the surface is placed in an oven, the drying temperature of the oven is set to 90°C, and it is dried for 5h. After the protective layer is cured, a new energy vehicle PCB coated with a protective film is obtained.
[0114] Then, various performance tests were performed on the prepared new energy vehicle PCB coated with the protective film:
[0115] First, the adhesion of the protective film of the prepared new energy vehicle PCB was tested according to the method in the national standard GB / T17-1979. The results showed that its adhesion was level one.
[0116] Then, the corrosion resistance of the protective film of the prepared new energy vehicle PCB was tested according to the method in the national standard GB / T1771-1991. The results showed that it could withstand neutral salt spray for about 1648 hours.
[0117] Finally, a thermogravimetric analyzer was used to test the high temperature resistance of the protective film for the prepared new energy vehicle PCB. The results showed that it could withstand a high temperature of about 765°C.
[0118] Comparative Example 1
[0119] A preparation process for a new energy vehicle PCB coated with a protective film, referring to the preparation steps of Example 1, with other conditions unchanged, only the silicone in step S5 is replaced by an equal amount of epoxy resin.
[0120] Then, various performance tests were performed on the prepared new energy vehicle PCB coated with the protective film:
[0121] First, the adhesion of the protective film of the prepared new energy vehicle PCB was tested according to the method in the national standard GB / T17-1979. The results showed that its adhesion was level three.
[0122] Then, the corrosion resistance of the protective film of the prepared new energy vehicle PCB was tested according to the method in the national standard GB / T1771-1991. The results showed that it could withstand neutral salt spray for 397 hours.
[0123] Finally, a thermogravimetric analyzer was used to test the high temperature resistance of the protective film for the prepared new energy vehicle PCB. The results showed that it could withstand a high temperature of about 175°C.
[0124] like Figure 3 As shown, by comparing the performance test results of the above embodiment 1, it can be seen that by modifying the epoxy resin once with silicone and then preparing the protective coating through subsequent steps, its adhesion, corrosion resistance and high temperature resistance can be better improved, thereby better protecting the PCB board and extending the service life of the PCB board.
[0125] Comparative Example 2
[0126] A preparation process for a new energy vehicle PCB coated with a protective film, referring to the preparation steps of Example 1, with other conditions unchanged, only the carbon dioxide in step S5 is replaced by an equal amount of nitrogen.
[0127] Then, various performance tests were performed on the prepared new energy vehicle PCB coated with the protective film:
[0128] First, the adhesion of the protective film of the prepared new energy vehicle PCB was tested according to the method in the national standard GB / T17-1979. The results showed that its adhesion was level five.
[0129] Then, the corrosion resistance of the protective film of the prepared new energy vehicle PCB was tested according to the method in the national standard GB / T1771-1991. The results showed that it could withstand neutral salt spray for about 954 hours.
[0130] Finally, a thermogravimetric analyzer was used to test the high temperature resistance of the protective film for the prepared new energy vehicle PCB. The results showed that it could withstand a high temperature of about 655°C.
[0131] like Figure 4 As shown, by comparing the performance test results of the above embodiment 1, it can be seen that the protective coating prepared by introducing carbon dioxide to react for secondary modification and then undergoing subsequent steps can better improve its adhesion, corrosion resistance and high temperature resistance, thereby being able to better protect the PCB board and extend the service life of the PCB board.
[0132] Comparative Example 3
[0133] A preparation process for a new energy vehicle PCB coated with a protective film, referring to the preparation steps of Example 1, with other conditions unchanged, only the polyoxypropylene diamine in step S6 is replaced by an equal amount of secondary modified epoxy resin.
[0134] Then, various performance tests were performed on the prepared new energy vehicle PCB coated with the protective film:
[0135] First, the adhesion of the protective film of the prepared new energy vehicle PCB was tested according to the method in the national standard GB / T17-1979. The results showed that its adhesion was level one.
[0136] Then, the corrosion resistance of the protective film of the prepared new energy vehicle PCB was tested according to the method in the national standard GB / T1771-1991. The results showed that it could withstand neutral salt spray for about 1026 hours.
[0137] Finally, a thermogravimetric analyzer was used to test the high temperature resistance of the protective film for the prepared new energy vehicle PCB. The results showed that it can withstand a high temperature of about 725°C.
[0138] like Figure 5 As shown, by comparing the performance test results of the above embodiment 1, it can be seen that by adding polyoxypropylene diamine to prepare a protective coating, its corrosion resistance can be improved, thereby better protecting the PCB board and extending the service life of the PCB board.
[0139] Comparative Example 4
[0140] A preparation process for a new energy vehicle PCB coated with a protective film, referring to the preparation steps of Example 1, with other conditions unchanged, only the filler in step S6 is replaced by an equal amount of secondary modified epoxy resin.
[0141] Then, various performance tests were performed on the prepared new energy vehicle PCB coated with the protective film:
[0142] First, the adhesion of the protective film of the prepared new energy vehicle PCB was tested according to the method in the national standard GB / T17-1979. The results showed that its adhesion was level one.
[0143] Then, the corrosion resistance of the protective film of the prepared new energy vehicle PCB was tested according to the method in the national standard GB / T1771-1991. The results showed that it could withstand neutral salt spray for about 1533 hours.
[0144] Finally, a thermogravimetric analyzer was used to test the high temperature resistance of the protective film for the prepared new energy vehicle PCB. The results showed that it could withstand a high temperature of about 415°C.
[0145] like Figure 6 As shown, by comparing the performance test results of the above embodiment 1, it can be seen that by adding fillers to form a protective coating, its high temperature resistance can be better improved, thereby better protecting the PCB board and extending the service life of the PCB board.
[0146] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A preparation process for a new energy vehicle PCB coated with a protective film, characterized in that: The steps include: S1: Add calcium carbonate and sodium carbonate and mix Grind and mix gibbsite and carbon powder, then add calcium carbonate and sodium carbonate, and disperse at high speed, then add boric acid and water glass, and mix by ball milling to obtain a mixed slurry; S2: Pressing and sintering The mixed slurry is pressed, sintered in a hydrogen atmosphere, and then further sintered in an air atmosphere, and then crushed and ground to obtain porous alumina powder; S3: ball milling and slip casting Sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, carboxymethyl cellulose and deionized water are mixed, and then ball-milled with the porous alumina powder, and then slip-casted and sintered to obtain a ceramic substrate; S4: Paste copper foil and perform post-processing A thin layer of resin glue is evenly coated on the surface of the ceramic substrate, and then copper foil is attached to the upper and lower surfaces of the ceramic substrate coated with the resin glue to obtain a foil-clad board, and then the foil-clad board is processed through a post-process to obtain a precursor PCB board; S5: Silicone and carbon dioxide modified epoxy resin The epoxy resin, the organosilicon, the catalyst and the deionized water are mixed, heated and stirred to react, so as to obtain a primary modified epoxy resin, and then carbon dioxide is introduced into the primary modified epoxy resin to continue the reaction, so as to obtain a secondary modified epoxy resin; S6: Prepare and spray protective coating The secondary modified epoxy resin is mixed with polyoxypropylene diamine, a leveling agent, a defoaming agent, a dispersant and a filler to prepare a protective coating, and then the protective coating is evenly sprayed on the surface of the precursor PCB board. After drying and curing, a new energy vehicle PCB coated with a protective film is obtained.
2. The preparation process of a new energy vehicle PCB coated with a protective film according to claim 1, characterized in that: Step S1 of adding calcium carbonate and sodium carbonate and mixing them specifically comprises the following steps: S1.1: Add gibbsite and carbon powder into a grinder at a mass ratio of 10-12:1 and grind for 2-3 hours to obtain a primary mixed powder; S1.2: Open the discharge valve of the grinder and pour the above-mentioned primary mixed powder into the high-speed disperser. When the gravity sensor in the high-speed disperser detects that the gravity in the machine begins to increase, the gravity sensor sends a signal to the controller; S1.3: After receiving the signal sent by the gravity sensor, the controller controls the feeding component to add calcium carbonate and sodium carbonate into the high-speed disperser at a mass ratio of 1-2:1; S1.4: until the gravity sensor detects that the gravity in the machine is no longer increasing, the gravity sensor sends a signal to the controller again; S1.5: After receiving the signal sent by the gravity sensor again, the controller controls the high-speed disperser to disperse at a rate of 3000-4000 r / min for 30-50 min to obtain a secondary mixed powder; S1.6: The controller controls the discharging component of the high-speed disperser to start, pours the secondary mixed powder into the ball mill, and then adds boric acid and water glass into the ball mill, and ball mills for 1-2 hours to obtain a mixed slurry.
3. The preparation process of a new energy vehicle PCB coated with a protective film according to claim 2, characterized in that: The pressing and sintering in step S2 specifically includes the following steps: S2.1: injecting the mixed slurry obtained in step S1.6 into a mold, and then pressing it with a uniaxial press at a pressure of 80-100 MPa to obtain a compact; S2.2: placing the compacted body in a sintering furnace, and then starting the ventilation assembly to extract the air in the sintering furnace through the ventilation assembly, and then replenishing dry hydrogen into the sintering furnace; S2.3: until the air pressure sensor in the furnace detects that the air pressure in the furnace returns to the initial state, the air pressure sensor sends a signal to the controller; S2.4: After receiving the signal sent by the air pressure sensor, the controller controls the ventilation component to close, and controls the sintering furnace to heat at a temperature of 1500-1800°C for 1-2h; S2.5: Keeping the heating temperature unchanged, the controller controls the ventilation component to open, exhaust the gas in the furnace through the ventilation component, and then replenish dry air into the furnace; S2.6: until the air pressure sensor in the furnace detects that the air pressure in the furnace returns to the initial state, the air pressure sensor sends a signal to the controller again; S2.7: After the controller receives the signal sent by the air pressure sensor again, it controls the sintering furnace to continue sintering for 1-2 hours to obtain a porous alumina compact; S2.8: Place the porous alumina compact in a crushing and grinding machine to crush and grind the porous alumina powder.
4. The preparation process of a new energy vehicle PCB coated with a protective film according to claim 3, characterized in that: The ball milling and slurry injection molding in step S3 specifically includes the following steps: S3.1: Sodium dodecyl sulfate, hexadecyl trimethyl ammonium bromide, carboxymethyl cellulose and deionized water are added into a mixing tank in a volume ratio of 20-22:13-15:8-10:40-50, and stirred to obtain a mixed solution; S3.2: Open the discharge valve of the crushing and grinding machine, pour the porous alumina powder obtained in step S2.8 into the ball mill, and add the above mixed solution into the ball mill, and ball mill for 30-40 minutes to obtain a mixed slurry; S3.3: pouring the mixed slurry into a plaster mold for slurry injection molding, and after demoulding, obtaining a slab material; S3.4: placing the above-mentioned slab material into an oven for drying, and then placing the dried slab material into a sintering furnace for sintering at 1500-1600° C. for 2-3 hours to obtain a ceramic substrate.
5. The process for preparing a new energy vehicle PCB coated with a protective film according to claim 1, characterized in that: Step S5 wherein the organosilicon and carbon dioxide respectively modify the epoxy resin comprises the following steps: S5.1: Add epoxy resin, organosilicon, catalyst and deionized water into the reactor, and then introduce nitrogen into the reactor until all the air in the reactor is exhausted; S5.2: Turn on the heater and stirrer in the reactor, heat and stir at a temperature of 100-120°C and a rate of 300-400 r / min, react for 3-5 hours, extract the catalyst with high-purity water 2-4 times, and then perform reduced pressure distillation to obtain a primary modified epoxy resin; S5.3: Add the primary modified epoxy resin and tetrabutylammonium bromide into a high-pressure reactor, and then introduce carbon dioxide into the reactor until all the air in the reactor is exhausted; S5.4: Start the high-pressure reactor, heat and stir, and continue to introduce carbon dioxide into the reactor until the pressure in the reactor reaches 1.6-2.2 MPa. React for 3-4 hours to obtain a secondary modified epoxy resin.
6. The process for preparing a new energy vehicle PCB coated with a protective film according to claim 5, characterized in that: Step S6 of preparing and spraying the protective coating specifically includes the following steps: S6.1: Add the secondary modified epoxy resin obtained in step S5.4 into a mixer, and then add polyoxypropylene diamine, a leveling agent, a defoamer, a dispersant and a filler into the mixer, and stir at a rate of 1000-1200 r / min for 1-2 hours to obtain a protective coating; S6.2: Spray the protective coating evenly on the surface of the front drive PCB board by an automatic spraying machine to form a protective layer; S6.3: Place the precursor PCB sheet with a protective layer on the surface in an oven, set the oven drying temperature to 70-90°C, dry for 3-5 hours, and after the protective layer is cured, obtain a new energy vehicle PCB coated with a protective film.
7. The process for preparing a new energy vehicle PCB coated with a protective film according to claim 5, characterized in that: The organic silicon is prepared by mixing diphenylsilanediol and DC-3074 in a mass ratio of 1:2-3.
8. The process for preparing a new energy vehicle PCB coated with a protective film according to claim 5, characterized in that: The catalyst is dibutyltin dilaurate.
9. The process for preparing a new energy vehicle PCB coated with a protective film according to claim 6, characterized in that: The atomizing valve pressure of the automatic spraying machine is 0.4-0.6MPa, the moving speed of the glue valve is 40000-48000μm / min, the height of the atomizing valve from the PCB board is 12-15mm, and the spraying speed is 80000-100000μm / min.
10. A new energy vehicle PCB coated with a protective film, characterized in that: It is prepared by the preparation process of a new energy vehicle PCB coated with a protective film as described in any one of claims 1 to 9.
Citation Information
Patent Citations
PROCESS FOR PREPARING AN EPOXY RESIN-BASED COATING FORMULATION, AND FORMULATION
BR132018014490E2
Environment-friendly corrosion resistant primer and preparation method thereof
CN106010239A